Outcome and Prognostic Factors of Pediatric Encephalitis in Thailand - Saengow, Vitchayaporn Emarach; Praphaphanthasak, Natnicha (Journal of Child Science, 2024)
Encephalitis, a severe central nervous system infection, poses significant morbidity and mortality risks. Etiologically, this condition can arise from infections or immune-mediated mechanisms, with varying causative agents across regions. Despite limited studies on pediatric encephalitis in Thailand, our retrospective cohort study aimed to discern the characteristics, outcomes, and prognostic factors influencing clinical results. We examined patients under 15 years of age admitted to Maharat Nakhon Ratchasima Hospital from January 1, 2007 to December 31, 2022, recording baseline data encompassing clinical manifestations, etiology, investigations, and treatments. The study defined outcomes in terms of morbidity, subsequent epilepsy incidence, and mortality rates evaluated via the modified Rankin Scale. Among 183 enrolled patients (age range 5 days to 15 years, mean age 7.4 years), males comprised 54.1%. Viral encephalitis (35.52%) and immune-mediated encephalitis (22.4%) emerged as the prevailing etiologies, with herpes simplex, dengue, and influenza virus as prominent viral pathogens. Anti-N-methyl-D-aspartame receptor encephalitis (56.1%) led among immune-mediated cases. Initially, 94.53% of patients displayed moderate-to-severe disability, while 45.7% exhibited clinical improvement within 6 months. Subsequent epilepsy ensued in 38.8% of cases, with an overall mortality rate of 19%, notably higher in viral encephalitis instances. Our findings underscore a predilection for viral pathogens in pediatric encephalitis cases, contributing to inferior prognoses. This study accentuates the necessity of understanding etiological patterns and prognostic markers to enhance clinical outcomes in this vulnerable population segment.
Keywords: pediatric encephalitis; etiology; outcome; prognostic factors